KARYA KOMPOSISI KARAWITAN MIRAT DANA - Saba, I Ketut (Institut Seni Indoensia Surakarta, 2010)
Art work creation, one of which is music composition, can occur because of a variety of internal and external motives. The music composition entitled Miratdana is created because of concern with various social agitations among a group of people who makes the society restless as shown in printed and electronic media. For example: murder, robbery, corruption and the similar deeds resulting in other’s loss of both property and even life. Music composition is one means of music that is expected to bring the people back into the right way because within it there are many song verses of life speech. The person, who had committed crime and tended to be anarchic, in my opinion, has forgotten a variety of life enjoyment that the God had bestowed as the universe creator. In Balinese the similar thing is called Miratdana. Keywords: fluctuation, forget yourself, awareness.